Gambaran Pengetahuan dan Sikap Ibu dalam Pemberian ASI Eksklusif sebagai Upaya Pencegahan Diare pada Anak Balita - Novi Eka Fitrah; Meri Neherta; Ira Mulya Sari (Journal of Telenursing (JOTING), 2023)
This study aims to see a picture of mothers' knowledge and attitudes in providing exclusive breastfeeding to prevent diarrhea in children under five. The method used is descriptive-analytic. The results of the study showed that the majority of mothers' knowledge was still lacking, namely 101 mothers (56.4%), mothers' attitudes were good, namely 126 mothers (70.4%), and 148 (82.7%) children under five were exclusively breastfed. The conclusion is that mothers' knowledge is still lacking, mothers' attitudes are positive, and most children under five already receive exclusive breast milk. Keywords: Children Under Five, Exclusive Breastfeeding, Knowledge, Attitude